1964
DOI: 10.1128/aem.12.6.475-478.1964
|View full text |Cite
|
Sign up to set email alerts
|

Milk-Clotting Enzymes From Microorganisms

Abstract: A total of 230 cultures of fungi and 43 cultures of bacteria, isolated from such sources as soil, butter, and milk, were screened for their milk-clotting activity. The fungi were cultivated on semisolid media, and the bacteria were grown in milk media in shake culture. Phytic acid, added as calcium phytate, was found to stimulate production of the enzyme in most of the bacterial isolates. Proteolytic activity was invariably found to be associated with the milk-clotting enzyme in bacterial isolates. There was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1972
1972
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Substrate activation for enzyme induction has been reported for milk clotting enzyme production by Absidia ramosa (Sannabhadti and Srinivasan 1977). MCP production from B. subtilis has been noted in skim milk medium (Srinivasan et al 1964), while Proflo and casein have been reported for Mucor (da Silveira et al 2005). As casein is the prime constituent of skim milk powder, its role in induction of enzyme synthesis is evident in these investigations (Thakur et al 1990).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Substrate activation for enzyme induction has been reported for milk clotting enzyme production by Absidia ramosa (Sannabhadti and Srinivasan 1977). MCP production from B. subtilis has been noted in skim milk medium (Srinivasan et al 1964), while Proflo and casein have been reported for Mucor (da Silveira et al 2005). As casein is the prime constituent of skim milk powder, its role in induction of enzyme synthesis is evident in these investigations (Thakur et al 1990).…”
Section: Discussionmentioning
confidence: 92%
“…Microbial rennets or MCPs possess distinct and worth while advantages not available with animal rennet in terms of cost, relatively unlimited and stable supplies, etc. (Sardinas 1972 (Srinivasan et al 1964;D'Souza and Pereira 1982) and others like Myxococcus (Poza et al 2003) and Nocardiopsis (Cavalcanti et al 2005) have also been reported as producers. The lack of research on bacterial MCP may be due to their higher PA leading to formation of bitter peptides (Channe and Shewale 1998).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A large number of microorganims are known to produce extracellular proteases, especially moulds [I -5, 10, 14, 18, 24,251. On the biochemical properties of some of those and other proteolytic enzymes has been reported [ l , 9,11,[17][18][19][21][22][23]26,27].…”
Section: Introductionmentioning
confidence: 99%